Review of the scientific journal “Red de Investigación Educativa - REDINE” (issn: 2244-7997) of the Universidad Centroccidental Lisandro Alvarado (Revista Electrónica REDINE, 2021)
The synthesis presented below is intended to know about the historical beginnings that gave rise to the REDINE magazine (ISSN: 2244-7997). In this sense, a group of teachers belonging to the different deaneries of the Universidad Centroccidental Lisandro Alvarado (UCLA), seeking answers to the concern of making their research and academic products known, grouped their ideas to found the legal bases and make the law a reality. creation of this prestigious investigative journal in the educational field. This coupled with the unconditional support of the governing authorities of the University and other professors who also gave their contributions and recommendations for the magazine to comply with all the necessary parameters. It is worth noting that REDINE emerged in 2009 and remains in force, complying with the various expectations expressed by those professionals who have given themselves the task of submitting their research papers, whose purpose is to generate a space for analysis and reflection in the educational field, as well as promoting the development of academic production carried out by experts in the area of ​​education and contributions that are produced from other disciplines. It is indexed / cataloged in Redib, Revencyt, Latindex, Actualidad Iberoamericana.
Keywords: educational research; academic production; educational environment; scientific journal; UCLA; Venezuela